Problems in the assimilation of gender behavior by children in a role-playing game - Bekenova Динара; Sekenova Балкумис (Рroblems of engineering and professional education, 2023)
It is well known that one of the key indexes of education is the gender parity index, because a non-discriminatory education benefits, both girls and boys and thus ultimately contributes to the development of equal relations between men and women. Therefore, in order to achieve good results in the field of pre-school education, relevant is the development and use in the work with children of differentiated forms of education for girls and boys based on their mental and physical differences.